The Role of the School Principal in Increasing Work Motivation and Work Discipline of Teachers in Elementary School - Arbert, Umi (PPSDP International Journal of Education, 2024)
This research aims to describe the role of the principal in increasing the work motivation and work discipline of teachers at SD Negeri Rahayu Kecamatan Jirak Kabupaten Musi Banyuasin. To collect the data needed for this research, it was carried out through observation activities, interviews with research respondents, and documentation studies related to the research problem being studied. The results of this research show that the principal of SD Negeri Rahayu Kecamatan Jirak Kabupaten Musi Banyuasin has improved the work motivation and work discipline of the teachers who teach at the school he leads. Meanwhile, the efforts made to increase teacher work motivation include giving rewards to teachers who carry out their duties well and providing allowances or incentives to teachers who carry out their duties well. The principal tries to create a peaceful and pleasant school environment so that teachers are more motivated to improve performance, providing opportunities for teachers to advance by involving teachers in educational and training activities, workshops, and seminars in order to improve teacher performance and careers, as well as establishing harmonious relationships with teachers who teach, and providing opportunities for teachers who teach at SD Negeri Rahayu Kecamatan Jirak Kabupaten Musi Banyuasin to participate in the nomination for school principal. Meanwhile, the principal’s efforts to improve work discipline are carried out by summoning teachers who lack discipline to be given guidance and direction and by giving strict sanctions in the form of warning letters to teachers who consistently violate the agreed discipline.